2019
DOI: 10.1152/japplphysiol.00665.2018
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive bouts of electrical stimulation-induced contractions alter ribosome biogenesis in rat skeletal muscle

Abstract: Ribosome biogenesis has been implicated in resistance exercise training (RET)-induced skeletal muscle hypertrophy. However, it is unclear how increasing bouts of RET affects ribosome content and biogenesis. This was investigated in the present study using simulated RET where rat skeletal muscle is subjected to increasing bouts of electrical stimulation. Sprague-Dawley rats were randomly assigned to the following seven groups: sedentary for 5 days (SED) or 6 wk (SED_6w), resistance-exercise trained with 1 bout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…Thus, activity of p70S6K might only be upregulated in the C group. In a recent study, three sessions of RE were reported to significantly increase the expression of rpS6 by 50% in the exercised leg compared to that in the sedentary leg, 18 which agrees with our results in the C group. However, in the FR group, the expression of total rpS6 did not increase with the three sessions of RE.…”
Section: F I G U R Esupporting
confidence: 93%
“…Thus, activity of p70S6K might only be upregulated in the C group. In a recent study, three sessions of RE were reported to significantly increase the expression of rpS6 by 50% in the exercised leg compared to that in the sedentary leg, 18 which agrees with our results in the C group. However, in the FR group, the expression of total rpS6 did not increase with the three sessions of RE.…”
Section: F I G U R Esupporting
confidence: 93%
“…The RE protocol was carried out as previously described (Kotani et al, 2019). Briefly, with rats under 3.5%–4.0% isoflurane deep sedation, we shaved the hair on the right leg of each rat off, and then the rat was secured by its right foot on a footplate in the prone posture.…”
Section: Methodsmentioning
confidence: 99%
“…The voltage (~30 V) and stimulation frequency (100 Hz) were adjusted to evoke maximal isometric contraction (Ogasawara et al, 2014). The frequency of RE bouts was every other day (48 h between bouts) in the 2B and 3B groups because previous studies showed that this frequency induces muscle hypertrophy in greater than or equal to12B (Kotani et al, 2019; Ogasawara et al, 2014, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations